Food-Based Dietary Guidelines Make Seafood a Priority, Sustainability an Afterthought. (29th May 2020) - Graham, Elizabeth; Thorne-Lyman, Andrew L; Love, Dave; Nussbaumer, Elizabeth; Bloem, Martin; Fry, Jillian; Pasqualino, Monica; Fanzo, Jessica
Abstract: Objectives: National food-based dietary guidelines (FBDGs) are adapted by governments reflecting their nation's food system and specific nutrition context, with varied approaches by country. Seafood is commonly included as one of many items in a "meat" or "animal-source" food group. It is currently unclear whether FBDG recommendations for seafood are achievable for the food supply, equitable for people, or sustainable for the planet. We seek to (1) Review the specific recommendations of national FBDGs related to seafood intake, quantifying the amount of seafood recommended for adults (2) Document the rationale for seafood consumption and mentions of sustainability (3) Estimate the supply required to meet recommendations and compare it with national fish production for each country. Methods: The Food and Agriculture Organization (FAO) FBDG database was used to identify 92 countries with officially recognized FBDGs. Extracted data include (1) Recommended consumption of seafood (amounts, standard portion size, frequency of consumption and species/type) and (2) Mentions of sustainability. To calculate the fish supply needed to fulfill recommendations, conversions from cooked portions to raw (grams) seafood weights were used. These converted figures were then compared against that from FAO FishStat and the Sea Around Us database, and gaps/surpluses by country were identified. Mentions of sustainability were evaluated in terms of specific mention of fish vs. more generic recommendations. Results: Out of 92 FBDGs, 77 mentioned seafood. Out of 40 high-income country's FBDG, 35 countries have a seafood servings per week recommendation, but only 23 provide serving size recommendations. Final presented results will illustrate the differences in the supply of seafood needed to meet recommended consumption levels. Sustainability was mentioned in eight guidelines independently of seafood and five additional mentioned seafood and sustainability together. Implications for sustainability of seafood production and global trade and nutritional status of populations will be discussed. Conclusions: Seafood is systematically noted for healthy diets but rarely based on sustainable limits nor linked to sustainable goals. Funding Sources: Johns Hopkins Bloomberg Distinguished Professor Fund, Johns Hopkins Center for a Livable Future.